Compromised vitamin D receptor signalling in malignant melanoma is associated with tumour progression and mitogen-activated protein kinase activity. Issue 5 (October 2018) - Hutchinson, Peter E.; Halsall, John A.; Popovici, Silvia; Papadogeorgakis, Eftychios; Osborne, Joy E.; Powley, Ian R.; Dasari, Deepthi; Saldanha, Gerald; Pringle, James H.
Abstract : The aims of this study were to investigate, in cutaneous malignant melanoma (MM), the integrity of nuclear vitamin D receptor (VDR) signalling, as implied by VDR subcellular location; to investigate the relationship between VDR and tumour progression and the inhibitory effect on VDR by mitogen-activated protein kinase (MAPK) overactivity. Archived tissue from 34 benign melanocytic naevi, 149 MMs and 44 matched metastases were stained by immunohistochemistry for VDR and a subset of primary MMs were stained for phosphorylated-extracellular signal-regulated kinase as a marker of MAPK activity. MM cell lines were investigated to show the subcellular location of VDR and cell viability in response to ligand±MAPK inhibitor. Benign melanocytic naevi showed mainly a strong nuclear VDR staining in contrast to MM where decreased nuclear and emergent cytoplasmic VDRs were associated with malignant progression in terms of dermal invasion and metastasis. MMs that retained exclusive nuclear VDR at the tumour base did not metastasize, a potentially important prognostic indicator. Decreased nuclear VDR correlated with increased cytoplasmic staining, suggesting the failure of nuclear entry as a primary cause of defective VDR signalling in MM. The histological subset analysis and MM cell line studies confirmed the inhibitory effect of MAPK activity on VDR signalling, but the pattern of VDR subcellular localization suggested failure of VDR nuclear entry as a primary effect of MAPK activity rather than direct inhibition of VDR-regulated transcription. Furthermore, high MAPK activity in tumours expressing cytoplasmic VDR was associated with worsened prognosis. Abstract : Supplemental Digital Content is available in the text.